Health workforce skill mix and task shifting in low income countries: a review of recent evidence - Auh Erica; Sparkes Susan P; Scheffler Richard M; Fulton Brent D; Vujicic Marko; Soucat Agnes (BMC, 2011)
Abstract Background Health workforce needs-based shortages and skill mix imbalances are significant health workforce challenges. Task shifting, defined as delegating tasks to existing or new cadres with either less training or narrowly tailored training, is a potential strategy to address these challenges. This study uses an economics perspective to review the skill mix literature to determine its strength of the evidence, identify gaps in the evidence, and to propose a research agenda. Methods Studies primarily from low-income countries published between 2006 and September 2010 were found using Google Scholar and PubMed. Keywords included terms such as skill mix, task shifting, assistant medical officer, assistant clinical officer, assistant nurse, assistant pharmacist, and community health worker. Thirty-one studies were selected to analyze, based on the strength of evidence. Results First, the studies provide substantial evidence that task shifting is an important policy option to help alleviate workforce shortages and skill mix imbalances. For example, in Mozambique, surgically trained assistant medical officers, who were the key providers in district hospitals, produced similar patient outcomes at a significantly lower cost as compared to physician obstetricians and gynaecologists. Second, although task shifting is promising, it can present its own challenges. For example, a study analyzing task shifting in HIV/AIDS in sub-Saharan Africa noted quality and safety concerns, professional and institutional resistance, and the need to sustain motivation and performance. Third, most task shifting studies compare the results of the new cadre with the traditional cadre. Studies also need to compare the new cadre's results to the results from the care that would have been provided--if any care at all--had task shifting not occurred. Conclusions Task shifting is a promising policy option to increase the productive efficiency of the delivery of health care services, increasing the number of services provided at a given quality and cost. Future studies should examine the development of new professional cadres that evolve with technology and country-specific labour markets. To strengthen the evidence, skill mix changes need to be evaluated with a rigorous research design to estimate the effect on patient health outcomes, quality of care, and costs.